2020
DOI: 10.1111/ajt.15580
|View full text |Cite
|
Sign up to set email alerts
|

Peritransplant eculizumab does not prevent delayed graft function in deceased donor kidney transplant recipients: Results of two randomized controlled pilot trials

Abstract: Funding information AlAnimal models and observational human data indicate that complement, including C5a, pathogenically participates in ischemia reperfusion (IR) injury that manifests as delayed graft function (DGF) following deceased donor kidney transplantation.We report on the safety/efficacy of anti-C5 monoclonal antibody eculizumab (Ecu) administered in the operating room prior to reperfusion, to prevent DGF in recipients of deceased donor kidney transplants in two related, investigator-sponsored, random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Again, the safety profile was good but pre-treatment with eculizumab had no effect on the incidence of DGF. Groups in these studies, however, were rather small [162]. Another anti-C5 antibody Tesidolumab (LFG-316, MorphoSys, Novartis) has currently entered phase 1 studies (NCT02878616).…”
Section: Complement Systemmentioning
confidence: 99%
“…Again, the safety profile was good but pre-treatment with eculizumab had no effect on the incidence of DGF. Groups in these studies, however, were rather small [162]. Another anti-C5 antibody Tesidolumab (LFG-316, MorphoSys, Novartis) has currently entered phase 1 studies (NCT02878616).…”
Section: Complement Systemmentioning
confidence: 99%
“…Eculizumab has also been used with promising results to treat C3 glomerulopathies ( 74 , 75 ) and antibody-mediated kidney transplant rejection ( 76 , 77 ). It has also been tested, but with no success, to prevent delayed kidney graft function (DGF) after transplantation ( 78 ). Several clinical studies are ongoing for other conditions, including HELLP syndrome (hemolysis, elevated liver enzymes, low platelet count - NCT04103489), and Guillain-Barre syndrome (NCT02029378).…”
Section: Complement Targeting Therapies Evaluated In Kidney Disordersmentioning
confidence: 99%
“…Kaabak et al [24] demonstrated that a single dose one hour prior to graft reperfusion in pediatric kidney recipients had better early graft function and biopsy scores, but the incidence of graft rejection did not differ between groups. A later study in 2019 also showed that the administration of eculizumab prior to organ reperfusion showed no difference in delayed graft, function, and survival at 6 months [25]. Another critical component of the complement cascade is C3, which can be produced by many tissues.…”
Section: Complement Activationmentioning
confidence: 99%